Attosecond XUV-pump/XUV-probe spectroscopy of glycine. Issue 7 (January 2020) - Lara-Astiaso, M; Palacios, A; Delgado, J; González-Vázquez, J; Decleva, P; Martín, F
Synopsis: We theoretically describe the outcome of an attosecond XUV pump-probe experiment in the smallest amino acid, glycine. We accurately evaluate the ionization amplitudes for the pump and the probe pulses. The molecular wave packet is then time-propagated using a trajectory-based Surface Hopping approach, accouting for the momentum distributions of the nuclei. Experimentally measurable photoelectron spectra are retrieved.